The Islamic manuscript tradition ten centuries of book arts in Indiana University collections - Gruber, Christiane J. 1976- (Indiana University Press, 2010)
Over the course of ten centuries, Islam developed a rich written heritage that is visible in paintings, calligraphies, and manuscripts. The Islamic Manuscript Tradition explores this aspect of Islamic history with studies of the materials and tools of literate culture, including pens, inks, and paper, Qur'ans, Persian and Mughal illustrated manuscripts, Ottoman devotional works, cartographical manuscripts, printed books, and Islamic erotica. All of the paintings, calligraphies, and manuscripts discussed here are held in collections at Indiana University